2020
DOI: 10.1101/2020.03.22.20040840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An alarming high prevalence of resistance associated mutations to macrolides and fluoroquinolones in Mycoplasma genitalium in Belgium: Results from samples collected between 2015-2018

Abstract: Objectives: The number of reported cases of multi-resistant Mycoplasma genitalium (Mg) is increasing globally. The aim of this study was to estimate the prevalence of macrolide and possible fluoroquinolone resistance associated mutations (RAMs) of Mg in Belgium. Methods: The study was performed retrospectively on two sets of Mg positive samples collected in Belgium between 2015-2018. The first set of samples originated from routine surveillance activities and the second set came from a cohort of men who have … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Another study from Belgium (from 2015 to 2018) examined levels of fluoroquinolone-resistance-associated mutations, but participants were not stratified by symptom status and either sex or sexual behaviour [31]. Both the levels of clinically relevant parC SNPs and dual-class resistance in asymptomatic male and female patients was 21.5 % [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from Belgium (from 2015 to 2018) examined levels of fluoroquinolone-resistance-associated mutations, but participants were not stratified by symptom status and either sex or sexual behaviour [31]. Both the levels of clinically relevant parC SNPs and dual-class resistance in asymptomatic male and female patients was 21.5 % [31].…”
Section: Discussionmentioning
confidence: 99%
“…MSM are a population who already experience high levels of macrolide-resistant M. genitalium, and any increase in fluoroquinolone resistance may result in dual-class-resistance strains, for which very limited treatment options are available [30]. Limited data are available on the trends and factors associated with fluoroquinolone-resistant M. genitalium in MSM [18,31], particularly asymptomatic MSM. This study analyses clinical samples obtained from the MnM study of M. genitalium in asymptomatic MSM [7], and aims to (i) determine the levels of fluoroquinolone and dual-class resistance in the cohort, (ii) explore any clinical and behavioural factor associations with fluoroquinolone resistance in M. genitalium, and (iii) determine the distribution of antibiotic resistance among M. genitalium mgpB sequence types (STs).…”
Section: Introductionmentioning
confidence: 99%
“…7 Resistance to fluoroquinolones in the Belgian community has been reported for several pathogens such as Streptococcus pyogenes, Helicobacter pylori, Mycoplasma genitalium and Escherichia coli . 8–12 Although the fluoroquinolone use expressed in DID decreased from 2.77 in 2012 to 2.17 in 2017, this number still remains too high in comparison to fluoroquinolone use in Europe with an average of 1.47 DID calculated from 27 countries in 2017. 13…”
Section: Introductionmentioning
confidence: 99%
“…The resistance prevalence estimates from both countries were derived from relatively old studies used in the systematic review (9). More recent studies have found a much higher prevalence of macrolide resistance in both countries (74% and 58%, respectively) (35, 36). These limitations mean that the results should be viewed with caution and require further validation.…”
Section: Discussionmentioning
confidence: 98%